Case Report: Identification of a Novel Heterozygous Missense Mutation in COL4A3 Gene Causing Variable Phenotypes in an Autosomal-Dominant Alport Syndrome Family - Hu, Yanglin; Li, Wei; Tian, Lulu; Fu, Shuai; Min, Yonglong; Liu, Jia; Xiong, Fei (Frontiers in Genetics, 2022)
Abstract: Alport syndrome (AS) is a genetic kidney disease of basement membrane collagen disorder accounting for approximately 2% of ESRD patients. Next generation and whole-exome sequencing method is increasingly frequently used as an efficient tool not only for the diagnosis of AS but also for the establishment of genotype-phenotype correlation. We herein report the identification of a novel heterozygous missense mutation in COL4A3 gene (c.G3566A: p.G1189E) causing variable phenotypes in a ADAS Family based on the combination of clinical, histologic, pedigree, and genetic sequencing information. The proband is a 48 years old Chinese woman suffering from persistent subnephrotic proteinuria and intermittent hematuria without renal function impairment over a 10-year time-span. Renal biopsy showed diffuse thin basement membrane and focal interstitial foam cells infiltration. The proband’s mother progressed to end-stage renal failure and the proband’s sister presented with subnephrotic proteinuria and intermittent hematuria as well. AS was highly suspected and confirmed by genome sequencing which revealed a novel heterozygous missense mutation in COL4A3 gene (c.G3566A: p.G1189E) in all the affected family members although their current medical conditions vary significantly. Our present finding emphasizes the significance of next generation sequencing technology for genetic screening which gives us an accurate clinical diagnosis of ADAS patients. And the identification of c.G3566A as a new ADAS-related mutation contributes to both genetic diagnosis of ADAS and further functional study of COL4A3.The variable phenotypes from the same genotype of our case also provide more information to genotype-phenotype correlation study.